Identification of Active Compound from Mitragyna speciosa Leave as Antiinflammation Agent: In Silico Study. - Ihsanul Arief; Erwan Kurnianto (Acta Chimica Asiana, 2022)
The study aims to identify the most responsible compound for the antiinflammation activity from Mitragyna speciosa leaves. Seventeen compounds previously reported to have been isolated from the leave were virtually screened against human 5-lipoxygenase protein and analyzed according to their binding energies. The native ligand used was arachidonic acid, and mitragynine was found to be the strongest binding compound (Pubchem ID: 3034396). In addition, ADMET profiling shows that mitragynine was not violating Lipinski’s rule of five and was not toxic.